Pyramids - Filer, Joyce (OUP E-Books., 2005)
Telling the story of the pyramids from their earliest beginnings, this volume describes not only the pyramids themselves but the whole complex of temples and walls that surrounded every one, and the stories of the kings and builders who created them.